The Interplay Between Words and Images in Line™ Instant Messaging Service: A Multimodal Analysis - Wildan Fachdiansyah (Passage, 2016)
The phenomenon of multimodal text in social media and instant messaging service is a challenge for linguists in analyzing today’s conversations which were traditionally dominated by verbal texts. Drawing upon the system of image-text relations proposed by Martinec and Salway (2005), this study focused on the interplay between words and images in students’ LINE conversations. It analyzed the status and logico-semantic relations and how those relations affect the meaning-making process in the conversations. This study employs descriptive qualitative method. This study found that the interplay between words and images in selected LINE conversations realized two status relations, which were equal-independent and unequal-image subordinate to text. The interplay between words and images in LINE conversations also realized three logico-semantic relations, which were extension, exemplification-image more general, and exposition. Both the stickers and verbal expressions were conveyed the meaning equally. Not all stickers were followed by verbal expressions, nevertheless, the participants still understand them. Based on the interviews, the stickers help the participants to visualize the facial expressions and gestures their friends used when communicating with them.Keywords: sexuality, conditioning, young adult dystopian, Delirium